The Dangers of Drugs and Strategies to Overcome Them at MTs Sunan Giri, Triwung Kidul Village, Kademangan District, Probolinggo - Wahibatul, Maghfuroh; Wawan, Susilo; Edy, Sumarno (Abdi Masyarakat, 2023)
In Indonesia, the problem of drug use is currently quite worrying. Probolinggo's experience of the phenomenon of juvenile delinquency is not much different from other big cities. Currently there are many kinds of juvenile delinquency, such as tardiness, speeding, drug use, premarital sex, brawls between teenagers, and others. Every year, many parties, including the public and private sectors, as well as individuals and institutions, undertake mitigation efforts. However, given the current situation, drug use in society continues to pose a threat to Indonesia's younger generation. In order to protect the future of the Indonesian nation, the Indonesian people must not give up in their efforts to eradicate and control drug trafficking. However, this journal needs to step up their efforts to stop juvenile crime. Based on this, we, the implementing team, are trying to prevent drugs in the community and provide understanding to the children of MTS Sunan Giri in Triwung Kidul Village, Kademangan District, Probolinggo City. This activity was attended by grade 9 students as well as staff members and the teacher council participated in this activity.